Enhanced sun protection of nano‐sized metal oxide particles over conventional metal oxide particles: An in vitro comparative study. (24th March 2014) - Singh, P.; Nanda, A.
Synopsis Background A systematic and detailed study has been designed and conducted, taking into account some of the proposed benefits such as increased efficiency, transparency, unique texture, protection of active ingredient and higher consumer compliance of cosmetics containing nano‐sized metal oxides. Methods This study also presents an in vitro method to determine sun protection factor of the investigational sunscreen cream samples containing zinc oxide and titanium dioxide with a varied range of particle size. Finally, a comparative study has been conducted between metal oxide particles, conventional as well as nanoparticles. Results All the skin cosmetics formulated were thermally stable with a pH ranging from 7.9 to 8.2. Moreover, the fatty acid substance content and residue were found to be analogous to the standard values in each skin cosmetic. The skin cosmetics containing the titanium or zinc oxide nanoparticles were found to have improved spreadability as compared to skin cosmetics containing conventional titanium or zinc oxide particles, respectively. All skin cosmetics were found to have uniform distribution of the particles. The sunscreen creams containing zinc oxide nanoparticles and titanium dioxide nanoparticles were found to have higher in vitro sun protection factor (SPF of 3.65 for ZnO nanoparticles and 4.93 for TiO2 nanoparticles) as compared to that of sunscreen creams containing conventional zinc oxide particles (SPF = 2.90) and conventional titanium dioxide (SPF = 1.29), clearly indicating the effect of reduction in particles size, from micro to nano, on the sun protection factor. Conclusion Good texture, better spreadability and enhanced in vitro SPF proved the advantageous role of nanoparticles in cosmetics.